Unemployment Equilibrium with Myopic Complete Information - Heller, Walter Perrin; Starr, Ross M. (Review of Economic Studies, 1979)
Walter Perrin Heller, Ross M. Starr; Unemployment Equilibrium with Myopic Complete Information, The Review of Economic Studies, Volume 46, Issue 2, 1 April 1979